Zakat contributions for Muallaf in Selangor / Muhamad Ikmal Aizad Mohd Rosli - Mohd Rosli, Muhamad Ikmal Aizad (Academy of Contemporary Islamic Studies (ACIS), 2017)
Zakat is one of the pillars of Islam. It is compulsory to all Muslim. Zakat also one of the instrument in Islam that will purify the Muslim wealth and help the needy. The obligation of zakat is from Allah commands through His Messenger, Prophet Muhammad SAW. The importance of zakat is to purify the Muslim wealth who pay the zakat. Besides, zakat also can help the eight recipient in daily life include Muallaf. This study aim to examine the effectiveness of the programs provided by Selangor Islamic Affairs Council (MAIS) in supporting Muallaf in Selangor. The researcher applies qualitative method to accomplish and gather of the fact for the study through interview with Selangor Islamic Affairs Council (MAIS) Muallaf Development and Management Unit Officer and data are analyzed. This study found that Selangor Islamic Affairs Council (MAIS) has a lot of contributions in supporting the Muallaf in Selangor by providing a lot of aids for zakat recipients goodness.